Development of Web Media Based on Google Sites and Its Effect on Student Learning Motivation in Economics Lessons for Students of SMA Negeri 8 Malang - Bashith, Abdul; Salfudin, Afif; Layali, Wildan Fikaromil; Wafa, Muhammad Ali (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED), 2024)
The objectives of this study are to: 1) create and assess Google Sites web-based learning materials and their viability; and 2) ascertain the effect of Google Sites online media use on the learning motivation of SMA Negeri 8 Malang City 11th grade students. Using the Borg and Gall paradigm, research and development (R&D) is the methodology employed. The process of designing a product may be broken down into seven simple stages: 1) research and data collection; 2) product creation; 3) product validation; 4) restricted trials; 5) revision; 6) user trials; and 7) final product manufacturing.Qualitative descriptive analysis and quantitative analysis are the two data analysis techniques used in this study. The findings demonstrated that 1) the creation of Google Sites online educational resources utilising the Borg and Gall paradigm was awarded.